SHEPHERDS, FATHERS, AND SHIPS: Ancient Greek Leadership Metaphors and Some Consequences - Christensen, Joël (Science et Esprit, 2022)
This paper applies Conceptual Metaphor Theory and Blending theory to explore the development of the phrase “people-eating king” across the background of cultural metaphors for leadership. First, I present a brief definition of the conceptual metaphor. Then I survey some primary metaphors for leadership in early Greek epic: the father-king, and the shepherd of the host. The investigation covers how various elements of each metaphor are activated in myth, creating an interconnection myths of Lykaon, who becomes a werewolf by eating people, Agamemnon, who sacrifices his own daughter, and Odysseus, who kills his own people. The stories around these leaders, I argue, emerge from anxieties about the consumptive potential of leadership through a convergence of separate conceptual metaphors.